Gilead - Robinson, Marilynne (London : Virago, 2004)
Reverend John Ames is dying in 1956 in Gilead, Iowa, and he is recording his family$1 (Bs story. Glory Boughton has returned to care for her dying father and soon her brother, Jack, the prodigal son, comes home, too.s
Originally published in hardcover: New York : Farrar, Strauss and Giroux, 2004.
ENH
Keywords: Conflict of generations -- Fiction; Reminiscing in old age -- Fiction; Children of clergy -- Fiction; Kansas -- Fiction; English literature